Emergência e desenvolvimento inicial de melão amarelo (Cucumis melo L.) usando diferentes substratosENTO INICIAL DE MELÃO AMARELO (Cucumis melo L.) - Silva, Gerarda Beatriz Pinto da; Barros, Geovânio Lima; Silva, Állisson Rafael Ferreira; de Medeiros, Priscilla Vanúbia Queiroz (Agrarian, 2013)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> In the production of seedlings of muskmelon is little information about the use of substrates for obtaining quality seedlings. Thus the objective was to evaluate the emergence and early development of melon seedlings grown in different types of substrates. The experiment was conducted in a greenhouse at the Department of plant Sciences, Universidade Federal Rural do Semiárido - UFERSA, located in the city of Mossoró-RN. The experimental design was randomized where they were deployed six treatments consisting of different substrates Solaris®, arisco soil, vermiculite, arisco soil + goat manure (2:1), arisco soil + Polifértil® (2:1) and Solaris® + goat manure (1:1). Yellow melon seeds were sown in polystyrene trays on the seventh day after sowing, were evaluated: emergency speed index, percentage of emergence, plant height, followed by determining the dry weight of shoots and roots. The shoot development of melon was favored mainly by the substrate containing arisco soil + goat manure in a 2:1 ratio, and also the mixtures containing Polifértil ® and Solaris®. The other parameters were not influenced by the substrate.